Rasionalitas Masyarakat Surabaya Dalam Pengajuan Istbat Nikah: (Studi Kasus di Pengadilan Agama Surabaya) - Mulyani, Sri; Rohman, Abid (Jurnal PUBLIQUE, 2022)
Marriage may have a different definition for each person, some consider it a necessity, some consider it a complement to faith. In Islam, marriage is done not only to increase offspring but is a fitrah for us as humans and a Muslim carries out the mandate of responsibility in the form of a family. To get married in a legal country like Indonesia, you must first get state recognition by recording it in the form of a marriage certificate. Marriage registration aims to create order in society. This is an effort that is regulated through legislation to protect a marriage. Some people may still carry out unregistered marriages for their own reasons, but the fact that without valid proof of marriage will lead to unclear rights of husband and wife, child custody, difficulties in managing citizenship administration, and this causes no legal protection to protect marriages. This reminds us of how important marriage registration is. Based on this thought, a brief study was conducted to determine the extent of Surabaya's public awareness of the importance of registering marriages through a case study at the Surabaya Religious Court. This paper uses qualitative methods and descriptive analysis of the results of interviews with informants.